1. Incidence of Nosocomial COVID-19 in Patients Hospitalized at a Large U.S. Academic Medical Center. (31st December 2020) - Rhee, Chanu; Baker, Meghan; Vaidya, Vineeta; Tucker, Robert; Resnick, Andrew S; Morris, Charles; Klompas, Michael
Abstract: Background: Many patients are avoiding essential care for fear of contracting Covid-19 in healthcare settings. However, the incidence of nosocomial Covid-19 infection in U.S. acute care hospitals is unknown. Methods: We conducted an observational study of all patients admitted to Brigham and Women's Hospital in Boston, Massachusetts between March 7 (when the first Covid-19 patient was admitted) and May 30, 2020. During this period, a comprehensive infection control program was implemented including dedicated Covid-19 units with airborne infection isolation rooms, personal protective equipment (PPE) in accordance with CDC recommendations, PPE donning and doffing monitors, universal masking, restriction of visitors, and liberal RT-PCR testing of symptomatic and asymptomatic patients. We reviewed the medical records of all patients who tested positive for SARS-CoV-2 by RT-PCR on hospital day 3 or later or within 14 days of hospital discharge to determine whether infection was community or hospital-acquired based on timing of RT-PCR tests, clinical course, and exposures. Results: Over the 12-week period, 9, 149 patients were admitted, in whom 7, 394 SARS-CoV-2 RT-PCR tests were performed and 697 Covid-19 cases were confirmed, translating into a total 8, 656 days of Covid-19-related care (Figure ). The inpatient Covid-19 census peaked at 171 on April 21. Twelve of the 697 Covid-19 patients (1.7%) were first diagnosed by RT-PCR on hospital day 3 or later (median 4 days, range 3–15 days). Of these, only one was deemed hospital-acquired and was most likely acquired from his pre-symptomatic spouse who was visiting daily and diagnosed with Covid-19 before visitor restrictions were implemented. Amongst 8, 370 non-Covid-19 patients discharged through June 17, 11 (0.1%) subsequently tested positive within 14 days (median time to diagnosis 6 days, range 1–14). Only one was deemed likely to have been hospital-acquired, albeit with no known exposures. Figure. Timeline of implementation of major infection control policies and cumulative number of hospitalized COVID-19 cases (total and hospital-onset) Conclusion: Nosocomial Covid-19 infection was exceedingly rare during the height of the pandemic in a hospital with rigorous infection control measures. Our findings may inform practices in other institutions and provide reassurance to patients regarding the safety of receiving care in acute care hospitals. Disclosures: All Authors : No reported disclosures